Construction quantity surveying a practical guide for the contractor's QS - Towey, Donald (Wiley-Blackwell, 2012)
"This book demonstrates that Quantity Surveying is not limited to working behind a desk measuring trade works from drawings & quantifying materials, but is in fact a dynamic and central role within the overall management of construction projects. With an introductory chapter defining the profession & examining the role it plays in the construction industry, the book is then divided into two parts, which cover working on behalf of a client and for a contractor respectively. The chapters cover the full range of activities a QS is likely to encounter, such as cost planning, measurement, procurement and project management"--